Rapid quantification of histamine in human psoriatic plaques using microdialysis and ultra high performance liquid chromatography with fluorescence detection - Guihen, Elizabeth; Ho, Wen Lyn; Hogan, Anna-Marie; O’Connell, Marie-Louise; Leahy, Martin J.; Ramsay, Bart; O’Connor, William T. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2012)
► Development of a rapid and ultra-sensitive liquid chromatographic method for the separation and detection of histamine. ► This represents one of the fastest reported separations of histamine using fluorescence detection. ► Intracutaneous histamine was measured 70 min after catheter implantation, a second fraction was collected 190 min after implantation and revealed similar levels with no difference in intracutaneous histamine between the control, peri-lesional and lesional skin regions. ► When combined with a novel rapid sensitive analytical method microdialysis may be used to explore the role of mast cells in psoriasis. Psoriasis is a chronic skin disease resulting from abnormal immune function and is characterized by the presence of scaly psoriatic plaques which are areas of inflammation and excessive skin production [1]. The psoriatic plaques contain mast cells which are increased in number in the uppermost dermis of the psoriatic lesion and which may play a role in the initiation and maintenance of the lesion. These processes are thought to be mediated via the local release of histamine along with other mediators from the mast cells; however their precise role still remains a mystery [2]. Our study involved the development of a rapid and ultra-sensitive liquid chromatographic method for the separation and detection of histamine. To this end a state-of-the-art ultra high pressure liquid chromatography (UHPLC) system incorporating the latest technology in fluorescence detection system was employed which allowed for the rapid and reliable trace level detection of histamine in human derived microdialysate samples. This new reverse phase method utilized a sub-two-micron packed C18 stationary phase (50mm×4.6mm, 1.8μm particle size) and a polar mobile phase of ACN:H2O:acetic acid (70:30:0.05) (v/v). The column temperature was maintained at (30±2°C), the injection volume was (8μl), with a flow rate of (1.1ml/min). Dermal microdialysis was used to collect (20μl) samples from healthy, peri-lesional and lesional skin regions, in the forearms of a small cohort of subjects (n=6), and the ultra sensitive liquid chromatographic method allowed for nanomolar quantitation of histamine in 6.7min. To date this represents one of the fastest reported separations of histamine using fluorescence detection with very high chromatographic efficiency (258,000/m) and peak symmetry of (0.88). Prior to sample analysis being performed method linearity, precision and limit of detection (LOD) were investigated. The results showed that intracutaneous histamine measured at 70min after catheter implantation was (3.44±.52nmol) (mean±SEM) in non-lesional (control) skin and was not dissimilar to that observed in either lesional (3.10±.76nmol) or peri-lesional skin (2.24±.20nmol). A second fraction collected 190min after implantation also revealed similar levels with no difference in intracutaneous histamine observed between control (2.41±.56nmol), lesional (2.69±.54nmol), or peri-lesional skin (2.25±.50nmol).